PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Grand Mahendra Napitupulu; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the influence of corporate governance characteristics to corporate social responsibility disclosure (CSR Disclosure). Characteristics of corporate governance used in this study is independent commissioners, audit committee, public ownership, and foreign ownership. Sample of this study consists of 102 company from manufacturing sectors listed on the Indonesia Stock Exchange in 2011-2013. This research analyzes CSR disclosure in annual reports by the method of content analysis. Data analysis was performed with the classical assumption and hypothesis testing of regression method. The results show that independent commisioners, public ownership, and foreign ownership did not have significant influence to the CSR disclosure. Audit committee has significant influence to CSR disclosure.